fpr, a deficient Xer recombination site from a Salmonella plasmid, fails to confer stability by dimer resolution: comparative studies with the pJHCMW1 mwr site. - Tran, T; Sherratt, D; Tolmasky, M (2010)
Salmonella plasmid pFPTB1 includes a Tn3-like transposon and a Xer recombination site, fpr, which mediates site-specific recombination at efficiencies lower than those required for stabilizing a plasmid by dimer resolution. Mutagenesis and comparative studies with mwr, a site closely related to fpr, indicate that there is an interdependence of the sequences in the XerC binding region and the central region in Xer site-specific recombination sites.